Hakikat Manajemen Pendidikan Agama Islam Multikultural di Pesantren Multidimensi Al-Fakhriyah Makassar - Inayah, Siti Nur Inayah; Yusuf, Muhammad Yusuf (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2024)
This research was conducted at the Multidimensi Islamic boarding school of Al-Fakhriyah Makassar. This pesantren is a modern pesantren but does not leave the culture of Salafi style, which has diverse students from various tribes, races, ethnicities, social classes, different skin colors, and regional origins. As a result of this diversity, this pesantren must have good management. The purpose of this study is to explore and analyze the form of multicultural Islamic religious education management in the Multidimensi Islamic boarding school of Al-Fakhriyah Makassar. Researchers use qualitative research methods with a case study approach, data collection using participatory observation, structured and unstructured interviews, and documentation, and then the data is processed by analyzing it through an interactive model proposed by Miles and Huberman. The result of this study is that the management of multicultural Islamic religious education in the Multidimensi Islamic boarding school of Al-Fakhriyah Makassar runs quite effectively and efficiently; all activities are carried out well, and multicultural values have been seen, although there are still a handful of perpetrators of discrimination. According to researchers, this problem can be overcome by adding more supervision and attention and updating the management related to the organizing system. Keywords: Management, Pesantrent, Multicultural.